Odpowiedź :
[tex] - 10 - h = - 6 \\ - h = 4 \\ h = - 4[/tex]
[tex] - f + 9 = 4 \\ - f = - 5 \\ f = 5[/tex]
[tex]4 - t = - 3 \\ - t = - 7 \\ t = 7[/tex]
[tex] - r + 3 = - 8 \\ - r = - 11 \\ r = 11[/tex]
[tex] - x - 4 = 7 \\ - x = 11 \\ x = - 11[/tex]
[tex]3 - u = 6 \\ - u = 3 \\ u = - 3[/tex]
[tex] - y - 4 = - 2 \\ - y = 2 \\ y = - 2[/tex]
[tex] - 3 - b = 10 \\ - b = 13 \\ b = - 13[/tex]
[tex] - x + 7 = 12 \\ - x = 5 \\ x = - 5[/tex]
1.
[tex]-10-h = -6\\\\-h = -6+10\\\\-h = 4 \ \ /:(-1)\\\\\boxed{h = -4}[/tex]
2.
[tex]-f + 9 = 4\\\\-f = 4 - 9\\\\-f = -5 \ \ /:(-1)\\\\\boxed{f = 5}[/tex]
3.
[tex]4-t = -3\\\\-t = -3-4\\\\-t = -7 \ \ /:(-1)\\\\\boxed{t = 7}[/tex]
4.
[tex]-r+3 = -8\\\\-r = -8-3\\\\-r = -11 \ \ /:(-1)\\\\\boxed{r = 11}[/tex]
5.
[tex]-x-4 = 7\\\\-x = 7+4\\\\-x = 11 \ \ /:(-1)\\\\\boxed{x = -11}[/tex]
6.
[tex]3 - u = 6\\\\-u = 6-3\\\\-u = 3 \ \ /:(-1)\\\\\boxed{u = -3}[/tex]
7.
[tex]-y - 4 = -2\\\\-y = -2+4\\\\-y = 2 \ \ /:(-1)\\\\\boxed{y = -2}[/tex]
8.
[tex]-3-b = 10\\\\-b = 10+3\\\\-b = 13 \ \ /:(-1)\\\\\boxed{b = -13}[/tex]
9.
[tex]-x+7 = 12\\\\-x = 12 - 7\\\\-x = 5 \ \ /:(-1)\\\\\boxed{x = -5}[/tex]